2000
DOI: 10.1053/jvet.2000.7539
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Skin Staples With Sutures for Anastomosis of the Small Intestine in Dogs

Abstract: Skin stapling devices can be used to create technically simple, rapid, and safe end-to-end anastomoses in canine jejunum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
137
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(142 citation statements)
references
References 12 publications
2
137
1
2
Order By: Relevance
“…This fact may be explained by the thorough check of the suture tightness during surgery, when the protective role of the omentum could not manifest itself significantly; or conversely, spontaneous adhesion of the omentum to the site of suture occurred in spite of the fact that it was not intentionally fixed on the operated part of the intestine. This latter explanation is supported by findings of experimental studies in dogs, confirming that almost always following a surgical intervention in the intestine, adhesion of the omentum at the site of the intestinal wall suture was demonstrated (Ellison et al 1982;Bone et al 1983;Coolman et al 2000). The omentum positively affects intestinal wall healing, as it provides sufficient blood supply, lymphatic drainage, and by formation of fibrinous adhesions it prevents the leakage of the bowel content into the abdominal cavity (McLachlin and Denton 1973;Ellison 1989).…”
Section: Discussionmentioning
confidence: 73%
“…This fact may be explained by the thorough check of the suture tightness during surgery, when the protective role of the omentum could not manifest itself significantly; or conversely, spontaneous adhesion of the omentum to the site of suture occurred in spite of the fact that it was not intentionally fixed on the operated part of the intestine. This latter explanation is supported by findings of experimental studies in dogs, confirming that almost always following a surgical intervention in the intestine, adhesion of the omentum at the site of the intestinal wall suture was demonstrated (Ellison et al 1982;Bone et al 1983;Coolman et al 2000). The omentum positively affects intestinal wall healing, as it provides sufficient blood supply, lymphatic drainage, and by formation of fibrinous adhesions it prevents the leakage of the bowel content into the abdominal cavity (McLachlin and Denton 1973;Ellison 1989).…”
Section: Discussionmentioning
confidence: 73%
“…Coolman et al compared skin staples to suture for anastomoses of the small intestine in dogs [7,8] . They concluded that end-to-end intestinal anastomosis with a skin stapler is equivalent in burst strength, lumen circumference, and healing characteristics when compared to the traditional hand-sewn technique, and can be performed in significantly less time.…”
Section: Discussionmentioning
confidence: 99%
“…Les indications sont nombreuses : résection de tumeurs digestives, résection d'un segment ischémié du tube digestif suite à un volvulus, une strangulation, une intussusception, la pré-sence d'un corps étranger, ou suite à une première chirurgie digestive compliquée (entérotomie ou entérectomie). Plusieurs techniques d'anastomose sont décrites en chirurgie vétérinaire : les anastomoses termino-terminales par suture [1] ou agrafes cutanées [2] et l'anastomose latéro-latérale par pinces auto-sutures [1,[3][4][5]. L'anastomose terminoterminale par suture reste aujourd'hui la technique la plus utilisée.…”
Section: Discussionunclassified